UPAYA GURU DALAM MENINGKATKAN PEMAHAMAN MATERI PENDIDIKAN AGAMA ISLAM PADA SISWA KELAS VIIIDI SMP NEGERI 1 SAJAD - Hera Witriana; Ahmad Rathomi, H. Syaifudin (Adisam Publisher, 2024)
This thesis discusses teachers' efforts to increase understanding of Islamic Religious Education material for Grade 8 Students at SMP Negeri 1 Sajad. This research has three research objectives including the following; First, find out the methods used to increase understanding of Islamic religious education material for grade 8 students at SMP Negeri 1 Sajad. Second, find out how the media is used to increase understanding of Islamic religious education learning material for grade 8 students at SMP Negeri 1 Sajad. Third, find out the supporting and inhibiting factors for PAI material for grade 8 students at SMP Negeri 1 Sajad. This research uses a phenomenological approach while this type of research is qualitative research. There are three types of data collection techniques in this research, namely: Observation, Interview, and Documentation. Meanwhile, the data analysis techniques used are data reduction, data presentation, verification and drawing conclusions. Then the data validity checking technique used is triangulation and member check. The results of the research are: First, the method used to increase understanding of Islamic religious education material in grade 8 students at SMP Negeri 1 Sajad is divided into two, including the lecture method and the question and answer method. Second, the media used to increase understanding of Islamic religious education learning material for grade 8 students at SMP Negeri 1 Sajad is visual media. Third, supporting and inhibiting factors for PAI material for grade 8 students at SMP Negeri 1 Sajad include the following: 1) Supporting factors for increasing understanding of PAI material for grade 8 students at SMP Negeri 1 Sajad are: a) internal psychological factors for students having an interest learning and high learning motivation to improve understanding of PAI material. b) students' external social factors are influenced by the environment, family, teachers and friends. 2) The inhibiting factors in increasing understanding of PAI material for grade 8 students at SMP Negeri 1 Sajad are: a) internal physiological factors, such as physical imperfections or disabilities, poor hearing, poor understanding of the material. b) external psychological, namely lack of interest in learning. Meanwhile, non-social external factors are influenced by inadequate facilities, the environment, and lack of lesson time.